Study of the Application of '90s Nostalgic Appeal in Visual Elements of Marketing Media: Nintendo - Nur Syafira, Farah Adilla; Sujatmiko, Guguh; Cintya, Hedi Amelia Bella (ULTIMART Jurnal Komunikasi Visual, 2024)
During the digitalization era, business growth throughout the world is increasingly rapid, meaning that not all companies can survive due to the demands of entrepreneurs to adapt and implement marketing strategies that are much more effective and innovative. One approach to marketing strategy that is starting to emerge is to use nostalgic appeals to attract consumer attention. 'Nintendo' is one of the companies that has survived and developed creative ideas by using nostalgic elements effectively in its marketing. This research aims to examine the application of nostalgic appeal in visual elements in 'Nintendo' marketing media. This research uses research methods in the form of observation and analysis of selected Nintendo marketing media content that uses nostalgic elements, focus group discussions (FGD) with respondents to determine the effect of using nostalgic elements on attraction and buying interest and literature study. From the results of this research, it is known that 'Nintendo's' strategy of using its '90s nostalgic elements in its marketing has succeeded in getting a positive response from consumers. The visual elements analyzed include tonal colors, design elements, images and icons, and typography. Through these nostalgic visual elements, consumer loyalty to the company increases and triggers strong purchasing interest in regular consumers and new market segments. This shows that the use of nostalgic elements in the company's visual marketing media has succeeded in having its appeal and can be used as an effort to renew marketing strategies in rapid business competition. Keywords: nostalgia; visual elements; marketing; nintendo